2002
DOI: 10.1515/bmte.2002.47.s1a.360
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ubiquitous Computing in Personal Health Monitoring Systems

Abstract: A possibility to significantly reduce the costs of public health systems is to increasingly use information technology. The Laboratory for Information Processing Technology (ITIV) at the University of Karlsruhe is developing a personal health monitoring system, which should improve health care and at the same time reduce costs by combining micro-technological smart sensors with personalized, mobile computing systems. In this paper we present how ubiquitous computing theory can be applied in the health-care dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 3 publications
0
22
0
1
Order By: Relevance
“…The software solution proposed by this paper could have exciting and profound impact on the area of healthcare that is related to patients recently discharged from hospitals or clinics, patients in poor and rural areas of the world, and even the general public [25]. Patient-centric health data provided by patients could prove to add a wealth of new knowledge that we have never been able to analyze or act upon before.…”
Section: Discussionmentioning
confidence: 99%
“…The software solution proposed by this paper could have exciting and profound impact on the area of healthcare that is related to patients recently discharged from hospitals or clinics, patients in poor and rural areas of the world, and even the general public [25]. Patient-centric health data provided by patients could prove to add a wealth of new knowledge that we have never been able to analyze or act upon before.…”
Section: Discussionmentioning
confidence: 99%
“…There had been a great deal of research and systems related to health monitoring systems. Pervasive computing applications are available in plenty as the authors suggest in [10][11][12][13][14][15]. In [16], the authors suggested a context awareness health monitoring system.…”
Section: Related Workmentioning
confidence: 99%
“…Lifelogging may change how we use and share personal data [3], allowing us to look back over our lives or search through and organize past experiences. Much research has been carried out in this field in order to create lifelogging devices, which enable people to efficiently monitor locations they have visited [4], maintain health records [5], [6] and log numerous other aspects of their lives [7], [8], [9]. However, lifelogging raises a number of questions, such as what, where, when and who we can monitor, and who can monitor us.…”
Section: Introductionmentioning
confidence: 99%